Drilling of Hybrid Aluminum Matrix Composites using Grey-Taguchi Method - C. SARALA RUBI; J. UDAYA PRAKASH (INCAS Bulletin, 2020)
Drilling is a very important hole making process. It is very much useful for assembly of parts. Incorporation of hard ceramic particles into the matrix of metallic composites made them difficult to machine. So, it becomes inevitable to optimize the drilling parameters. The foremost objective of this research work is to fabricate Hybrid Aluminium Matrix Composites(AMCs) of LM6/B4C/Fly Ash with 3%, 6% & 9% by weight percentages of both reinforcements, equally using stir casting technique. The next objective is drilling of composites with feed, speed, drill and percentage of reinforcement as input process parameters at three levels each by Taguchi’s Design of Experiments approach. The final objective is to optimize the drilling process parameters for achieving low thrust force, low surface roughness and minimum burr height using the multi-objective Grey Relational Analysis. Results reveal that drill material plays a major role, being closely followed by feed and speed.